Policy Analysis of the Integration between Dapodik and the Online Student Admission System in Bojonegoro Regency - Kasbijanto, Kasbijanto; Mohammad Syahidul Haq; Amalia, Kaniati; Hazin, Muffarihul (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study is a literature review aimed at evaluating the policy related to the integration of the Basic Education Data (Dapodik) with the online New Student Admissions (PPDB) system in public junior high schools under the auspices of the Bojonegoro Regency Education Office. This integration is considered crucial for building a more open, effective, and accountable education system supported by accurate data. This study examines a number of related literature sources, regulations, and policy documents to explore the challenges, opportunities, and consequences of this policy on the implementation of online PPDB. The results of the study indicate that although the integration of data between Dapodik and online PPDB can strengthen data validity, improve data accuracy, and accelerate the selection process, its implementation still faces technical obstacles, limited human resource capacity, and disparities in facilities across schools. Therefore, it is necessary to improve coordination between relevant parties, strengthen the technical capabilities of school operators, and adapt regulations responsive to local conditions. The results of this study are expected to contribute as considerations in the development of policies for a more integrated and sustainable education system.